FENOMENA BAHASA SATIRE DALAM MEME DI MEDIA SOSIAL - Yufi Safwan Fajar (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
The satire style was chosen to express satire and criticism explicitly. In communicating on social media, satire is also used in making memes. The problem with this research is how satire language is in meme culture on social media. This research aims to reveal how political satire is discussed in memes on social media. The purpose of this study is to examine more deeply how the satire discourse is contained in pictorial texts or purely texts in social media memes. This research is interesting because the satire humor style contained in memes becomes a practical, absurd political, economic, educational, cultural, and other responsibility that can shift, eliminate, then reverse and bring up new discourses. This study uses a critical discourse analysis by Norman Fairclough, which identifies that the discourse can be a series of verbal and written words or a series of speech acts. With this knife of analysis, it was found that satire in memes on social media is used in the form of satire and criticism of things that are being viral and how these issues affect social media in the real world. Memes are not seen as silent, passive, and finished texts as they are produced. On the other hand, Memes are dynamic and moving strategies through comedy Satire.